If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3R + 6 = 13R + 8 Reorder the terms: 6 + 3R = 13R + 8 Reorder the terms: 6 + 3R = 8 + 13R Solving 6 + 3R = 8 + 13R Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Add '-13R' to each side of the equation. 6 + 3R + -13R = 8 + 13R + -13R Combine like terms: 3R + -13R = -10R 6 + -10R = 8 + 13R + -13R Combine like terms: 13R + -13R = 0 6 + -10R = 8 + 0 6 + -10R = 8 Add '-6' to each side of the equation. 6 + -6 + -10R = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -10R = 8 + -6 -10R = 8 + -6 Combine like terms: 8 + -6 = 2 -10R = 2 Divide each side by '-10'. R = -0.2 Simplifying R = -0.2
| 3(-x+4)+6x=2(2x-6)-x | | -4(1-y)+3(2y+3)=7y-10 | | 18+6y=10y-2 | | 2+3+4+5=15 | | 10y-2=6y+10-y | | 2+2=0 | | x-2+5+4=0 | | 3(3X-2)=21 | | x-2=x^2-1 | | 8y=y+7y | | .4x-.2(50+x)=-.4(50) | | 5y+2= | | y(3x-1)=4(x+2)-1 | | x^2-147=0 | | 8x+7y=16 | | 6(x+3)=3x+9 | | 6.8+1.6n=2.64 | | 6.8+1.6n= | | -8x^2(-10x^4+9x^3)= | | x^4-16x^2+63=0 | | (x+1)2=1 | | -4m+24-4(m-2)=6m-(2m-1)-5m+6 | | 2+8(t-9)=2(t+4)+6 | | S=-16t^2+676 | | 6a^3-5a^2-4a=0 | | -(6z-(17z+9))=9+(10z+10) | | 4m=36 | | 5(3z-1)-5(z+2)=6(z+1) | | 2(d-(2d+12)+9)=2(d+3) | | -5(d+1)-d-6=-6(d+4)+13 | | -9p-3(6-6p)=6(p-2)-28 | | 11(v+3)-2v=3(3v+4)-20 |